Evaluasi Dampak Kebijakan Pembangunan Jaringan Listrik Bawah Laut - Irma Ayu Sundari; Dian Kagungan (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2019)
Pisang Island is a tourist destination object that is a mainstay in the coastal region, is West Coastal District. There is an exotic and natural tourist destination. However, the facilities found in the Pisang Island area have not been able to support the superiority of tourism in it. This is caused by the absence of electricity to Pisang Island. Therefore, the Pesisir Barat District Government enthusiastically built the electricity network installation on Pisang Island. This research aims to find out how the impact of the construction of an underwater electricity network on Pisang Island. This type of research is descriptive research with a qualitative approach. To predict the impact that will occur from the construction of an undersea power grid on Pisang Island, considering that the development has not been fully realized by seeing the positive and negative impacts that will be caused, seen from three aspects is: (1) Social and cultural aspects, predicted to support development and introducing culture in Pisang Island, improving the quality of education, and predicted a negative impact, is the existence of socio-cultural changes to the community (2) Economic Aspects, predicted to increase economic income, increase tourism population and facilitate development to be carried out on Pisang Island, the negative impact is power shortages in other regions (3) Environmental aspects, the possibility is that there will be no damage to the marine ecosystem if the construction is in accordance with what has been determined. For this reason, it is necessary to do a number of things, is: 1. Conduct a more in-depth socialization policy with the community, 2. Make improvements/ developments related to the crossing mechanism to Pisang Island.